The Influence of Learning Media Flash Card and Picture in the Development of English to Improve Childhood Speaking Skills - Wani, Anis Syafa; Lubis, Yani; Rizky, Septiana (Journal of Multidisciplinary Science: MIKAILALSYS, 2023)
Early childhood has a strong curiosity, that's one of its characteristics. This curiosity can be overcome by using the media as a media application. Because learning English as a language that is widely used in the world today is quite a difficult task, especially for young children. However, there are many ways to make learning English easier, especially speaking skills, by using learning media, such as listening to children's songs, watching animated videos, and using application features on mobile phones. Learning media is anything that is used to increase the effectiveness of learning for each student. Through the development of technology, education and mass media, they can create a more attractive and efficient way of teaching for everyone, especially children. In early childhood, the media used certainly attracts more attention, such as the use of flash cards and pictures. This learning media causes the emergence of creativity for every child which is useful for improving their abilities, especially speaking skills, so that children are even more courageous to express their opinions using English.